Estimates of coefficients for bi-univalent Ma-Minda-type functions associated with $ \mathfrak{q} $-Srivastava-Attiya operator - Norah Saud Almutairi; Adarey Saud Almutairi; Awatef Shahen; Hanan Darwish (AIMS Mathematics)
In this article, we consider new subclasses of analytic and bi-univalent functions associated with the q-Srivastava-Attiya operator in the open unit disk. We obtain coefficient bounds for the Taylor-Maclaurin coefficients $ |a_2| $ and $ |a_3| $ of the functions of these new subclasses. Furthermore, we establish the Fekete-Szegö inequality for functions in the classes $ \mathcal{T}^{ε}_{τ, \mathfrak{q}, α}(ψ), \; \mathcal{KH}^{ε}_{τ, \mathfrak{q}, α}(δ, ψ), \text{and}\; \mathcal{A}^{ε}_{τ, \mathfrak{q}, α}(δ, ψ) $.